Analysis of age-related changes of anaerobic power in ice hockey - Kokinda, M.; Kandrac, R.; Cech, P. (Journal of Physical Education and Sport, 2020)
The purpose of this non-randomized cross-sectional study was to assess anaerobic power using the Wingate anaerobic test among youth and senior ice hockey players.The participants included 76 ice hockey players who were divided into three subgroups. Subgroup G1 included 30 senior players (aged > 20.0 years), and subgroup G2 included 23 under-20-year-old players (aged 18.0 to 19.99 years). Subgroup G3 included 23 under-18 players who were aged 16.0 to 17.99 years. In the season during which anaerobic power testing was conducted, most of the players played for the top senior ice hockey teams on a regular basis. Off-ice anaerobic power was assessed by the Wingate anaerobic test using the Monark 894E weight brake cycle ergometer. The statistical significance of age category-related differences for parameters related to the anaerobic power of the ice hockey players was determined using the results of a one-way analysis of variance (ANOVA 1x3) with subsequent multiple comparison of means by an LSD post hoc analysis. The rejection of the null hypothesis was assessed at the level of p< .05. Effect size was determined using Cohen`s "d" coefficient. The results showed that anaerobic capacity was statistically different according to age, and, in terms of practical significance, there was a large effect of age on the anaerobic parameters. There were neither a statistically nor practically significant difference in the parameters of anaerobic power and capacity between senior players and U20 players with the exception of the absolute values of peak anaerobic power.The results show that bicycle ergometer may be used to assess lowerbody anaerobic power, but for ice hockey norm-referenced databases need to be modified for the AirBike.